Business Plan For A Horse Training Center - Koskinen, Tiia (2020)
The objective of this thesis is to create a business plan for a horse training center located in North Karelia, Finland. The business plan focuses on the profitability of a new business by studying the cost structure of the different revenue streams in the horse training center and finding out the typical market prices for the services. The research is executed as a case study and it follows the definition of an empirical research. The empirical evidence is gathered and analyzed by using qualitative research methods. The interviews are conducted as semi-structured phone interviews. The business idea changed during the research process due to the findings from the interviews. At first, the idea was to import sport horses to Finland and sell them forward, but the services that remained in the final business plan are stall rental services, training young horses and coaching riders in North Karelia. The conclusion of the calculations for the horse training centre is that the business would be profitable.